GEOPHYSICAL DATA: ESTIMATING ORGANIC MATTER IN ROCKS - Karpenko, O.; Bashkirov, G.; Karpenko, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Hydrocarbon (HC) reserves expansion determines a necessity to enhance exploration efficiency due to the complexity of the geological environment in the undeveloped oil-and-gas fields. Ukraine is prospective to explore shale and tight rocks, which like oil-and-gas deposits in the United States, may contain considerable reserves of hydrocarbons. Thus, proper attention should be paid to geological and geophysical diagnosis of rocks with a high content of organic matter (OM) – kerogen. Recent research findings suggest that the total content of organic carbon is a direct indicator of the potential presence of shale gas reserves. The research into the geophysical methods applied to determine the content of OM in wells reveals their being inefficient, especially when they are applied to certain geological fields or are preceded by a limited number of logging techniques. Thus, the values of the apparent resistance indicating high gas content in the saturation zone opposite reservoirs are often misinterpreted to be an increase in the OM content. To counterbalance this, the authors propose a new non-electrical geophysical methodology of well logging and a technique for estimating OM content, both based on the use of a system of linear petrophysical equations. The methods are also based on Q. Passey and others' findings of natural gas distribution in shale formations enriched with OM. Organic content, clayiness, and the value of the total porosity of rocks are considered to be the unknown in petrophysical equations. Petrophysical coefficients are used either as prior evidence or as specially developed methods for their determination. The set of equations proposed is confined to petrophysical input parameters (the number of equations and the unknown, respectively); this is due to a small number of traditional methods of well logging. The approach being tested in a number of wells containing shale strata, and laboratory data being compared, the conclusion provides validated data interpretation for determining reservoir properties of rocks and organic matter content in them. In the future, the enhancement of this methodology may involve the development of methods to adjust petrophysical coefficient on core material via minimizing laboratory measurements.
Keywords: well logging; shale gas; organic matter; kerogen; porosity; clayiness